Disaster communications in a changing media world - Haddow, George D. (Butterworth-Heinemann, 2009)
Effective communication, via TV news or text messaging, can save lives during a disaster!
Keywords: Emergency management.; Disasters -- Press coverage -- Planning.; elektronické knihy; electronic books